UI Design for Wearable Devices - Vítor Manuel Mota Cardoso da Silva (2016)
Smartwatches have been around for some time now (Ranger 2015), but 2015 is the year this wearable technology will finally get its boom in terms of popularity and growth. Technology giants like Apple, Google and Samsung are betting on their own-line of products such as the Apple Watch, Android Wear and Gear respectively (Apple Inc 2015a; Google Inc 2015b; SAMSUNG 2015). All of these devices are computation capable electronics with very small touch capacitive screens, limited number of hardware buttons with varying screen sizes and even shapes. Our research focused mainly on these constraints and how to successfully develop user friendly GUI's for such small screens. The goal was to develop a model with guidelines to help developers provide easy to use and user friendly applications at a visual and interaction level to end users. To successfully achieve this, we first took a deep look at the available technology within these devices, including the framework each of the major platforms provide and the underlying hardware capabilities such as sensors like GPS, gyroscope, the use of the touch screen or microphone for user input and whether the shape of the device (round or squared) can have different effects on the design and usability. We also analyzed the impact of placement and arrangement of interface components having in mind that this technology, since it is a wearable watch, can be worn on both wrists and therefore will be used with only one hand that may obscure a different portion of the interface depending on which wrist the user uses it (Chandra and Raghunath 2000). Finally, to evaluate our model we built a prototype and put it to test with end users, collecting usage metrics and feedback on usability to further improve the original model.